Rare earth mining and consumption global trends and mining perspectives for the Mushugay Khudug deposit in southern Mongolia - R, Galbadrakh; K, Simon; T, Myanganbaatar; L, Nyam-Ochir; N, Tuvjargal; Ts, Myanganbayar; J, Davaasambuu; G, Woerner (Scientific transaction of the National University of Mongolia. Physics, 2022)
In this work the 3 ore body drill core samples. 6 host rock samples from the main ore body of the Mushugay Khudug REE deposit in southern Mongolia were selected as most representative samples and studied by XRD and ICP-MS. LA-ICP-MS method to evaluate elemental and structural composition data of the deposit. According to our determinations the main orebody of the Mushugay Khuduk deposit contain up to 130 kg/ton of REEs. Despite the moderate total mineable reserve the main ore body of the Mushugay Khuduk deposit might compete economically with world’s biggest REE mining deposits such as Bayan-Obo (Inner Mongolia. China) or Mountain Pass (California. USA) if consider the deposit’s higher REE grade and easier to mine local geological condition. The important advantage of the Mushugay Khuduk deposit is that the relative contents of most valuable HREEs Eu. Tb. Dy. and Lu are significantly higher than that of Mountain Pass or Rayan-Obo. The relative net content of these four elements is 0.1% for Mountain Pass and 0.4% for Bayan-Obo. while the ore samples of the Mushugay Khuduk deposit has 0.75% according to our determinations.